AB0797 Impairment of coronary microcirculation in patients with diffuse systemic sclerosis. (23rd January 2014) - Atzeni, F.; Gianturco, L.; Sarzi-Puttini, P.; Ricci, C.; Tommasoni, L.; De Gennaro Colonna, V.; Ferrario, P.; Epis, O.; Turiel, M.
Abstract : Background: An association between systemic autoimmune diseases (SADs) and atherosclerosis has been described in many connective tissue diseases, and is known to lead to increased cardiovascular (CV) morbidity and mortality. Systemic sclerosis (SSc) ischaracterised by multi-system organ inflammation, endothelial wall damage and vasculopathy (1). There are many markers of endothelial dysfunction and/or atherosclerotic risk, such as asymmetric dimethylarginine (ADMA), arterial stiffness parameters, carotid intima-media thickness (cIMT) and coronary flow reserve (CFR) assessed by means of trans-thoracic echocardiography (TTE). Objectives: The aim of this pilot study was to use various endothelial and atherosclerosis markers to identify early CV involvement in a group of SSc patients. Methods: The study involved 20 patients (two males, 18 females; mean age 52.96±12.51 years) with diffuse SSc but no signs or symptoms of CV disease (CVD), and 20 age- and gender-matched controls. All underwent a dipyridamole echocardiographic stress test which included a determination of CFR, and an evaluation of cIMT, arterial stiffness and plasma ADMA levels. Results: All the arterial wall measurements of the diffuse SSc group were significantly different from those of controls and both right and left cIMT, pulse wave velocity (PWV), and stiffness index β were also all significantly elevated in SSc patients compared to healthy controls (Table 1 ). Moreover, in patients with diffuse SSc CFR was significantly lower (P=0.0033) and plasma ADMA levels higher (P<0.0001) than in healthy controls (Table 1). Conclusions: This study showed that those SSc patients without any clinical evidence of CVD had subclinical atherosclerosis, which was suggested by early impairment of coronary microcirculation and macrovascular involvement. Disclosure of Interest: None Declared